INVESTIGATION OF THE ACCURACY OF THE POLAR METHOD OF SHOOTING RAIL CURVES - Korzhenevych, I. P.; Renhach, M. H.; Loshkarev, M. O. (Science and Transport Progress, 2006)
Questions of accuracy new polar way of shooting of railway curves are considered.